Superficial Necrolytic Dermatitis in a Dog - Markus Götze, Daniela; Mendes Götze, Marcelo; Cunha Bustamante Filho , Ivan; Clare Goulart de Carvalho, Flávia (Acta Scientiae Veterinariae, 2022)
Background: Superficial necrolytic dermatitis (SDN), hepatocutaneous syndrome (HCS), metabolic epidermal necrosis (MEN), and necrolytic migratory erythema (MEN) are useful terms to describe a disease that likely has a multifactorial etiopathogenesis. SDN is a rare and fatal disease characterized by skin lesions and liver disease. Common skin lesions include hyperkeratosis, fissures, erosion, ulceration, crusting, exudation from the paws, face, perianal regions, and pressure points. This case report aimed to report the case of a bitch that developed the rare Superficial Necrolytic Dermatitis disease, emphasizing the clinical signs of the disease, and the importance of complementary exams such as abdominal ultrasound and skin biopsy for the definitive diagnosis. Case: A 9-year-old, mixed-breed, neutered female was referred for clinical examination with 5 months history of hyperkeratosis and ulceration of the paw pads, presenting pain, lameness and weight loss. Abdominal ultrasound revealed a liver with heterogeneous echotexture, mixed echogenicity, irregular and poorly delimited margins with hypoechoic nodules throughout like honeycombs. The gallbladder was visualized with a moderately thick layer. Histological analysis confirmed the diagnosis of SND. Skin biopsies showed an increase in thickness of the epidermis due to irregular hyperplasia and proliferation of keratinocytes in the basal layer of the epidermis, pallor of the spinous layer of the epidermis and important parakeratosis. Due to the progression of the disease, significant worsening of the patient's clinical condition and pain, associated with the impossibility of cure, the animal was submitted to euthanasia. A necropsy was performed to allow assessment of the liver and pancreas. The biopsies showed a severe proliferative chronic hepatitis, steatosis and cholestasis associated with pancreatitis and necrotic multifocal proliferative fibrinopurulent areas in the pancreas. Discussion: Clinical signs such as lethargy, inappetence, weight loss, as well as the dermatological signs presented by this bitch are nonspecific clinical signs and require a deeper clinical, pathological and histopathological diagnostic investigation to reach the diagnosis of this disease. The definitive diagnosis is made on the basis of a characteristic honeycomb pattern in the liver or associated with a neoplastic finding in the pancreas on ultrasound examination and confirmed by histopathological evaluation of skin biopsies. Palliative treatment with corticosteroid anti-inflammatories, improvement in feed quality, with higher nutritional and protein intake and intravenous amino acid supplementation are suggested by some authors as treatment alternatives. However, not all owners can afford a costly lifetime treatment. With the progressive worsening of the condition, many owners opt for euthanasia as a way to shorten the suffering of the animal. This decision is not an easy one to make. Despite the poor prognosis of the disease, treatment options should be tried by veterinarians and owners prior to the option of euthanasia. However, new affordable nutritional and pharmacological strategies to treat or control the disease are needed in order to improve quality of life of SDN patients. Keywords: canine, bitch, SDN, hepatocutaneous syndrome, metabolic epidermal necrosis, necrolytic migratory, dermatopathy.